Kompetensi Guru PAI dalam Pembelajaran Berbasis Teknologi Informasi - Rohmad Ms. (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2013)
This research focuses on the problem of information technology-based teaching activities by teachers of Islamic education in the regent of Sidoarjo. The research concludes that the learning activity on the subject of Islamic education is very much conventional where teachers play the major role in acquiring knowledge, while students were not involved. The research also discovers that teachers do have good teaching qualifications given that they meet 12 out of 16 competences criterion set by the national standard authority on the subject. But they on the other hand, are weak in terms of pedagogic qualification considering that they meet only 12 to 17 out of 42 competences. The research finds that the ability and skill of the teachers in using technology such as computer, laptop, LCD and internet are among the main factors behind their competencies. Teachers of SMAN 1 in Krian, and SMKN 2 in Buduran are among those who are familiar with the information technology system. Meanwhile, the poor infrastructure and limited availability of information technology in such schools as SMAN in Tarik, SMAN 2 in Sidoarjo and Porong are the main factors that hamper the process of developing the teaching standard.